أساليب التعذيب والقسوة دراسة في مثيولوجيا الحـروب السومـرية والأكدية - بشار جمعة, احمد (Journal of College of Education, 2019)
The history of ancient Iraqi civilization is full of many military events illustrated by artistic scenes and cuneiform texts, which showed a series of wars and conflicts in the third millennium BC and the role of the gods in which to resolve the results of those wars by intervening directly or through the deputy who was entrusted with the task of governing her parish in the land These material results gave us an accurate description of the military policy of the rulers and kings of ancient Iraq to impose their authority on the rest of the other cities, whether to expand their kingdom or to form a unified central state, using various methods of torture and cruelty towards his opponents Individually or collectively, causing those wars, destruction of the cities of the plunder of wealth and infringement of civil and religious property.